white as a reporter gene to detect transcriptional silencers specifying position-specific gene expression during Drosophila melanogaster eye development. - Sun, Y.H.; Tsai, C.J.; Green, M.M.; Chao, J.L.; Yu, C.T.; Jaw, T.J.; Yeh, J.Y.; Bolshakov, V.N. (Genetics, 1995)
The white+ gene was used as a reporter to detect transcriptional silencer activity in the Drosophila genome. Changes in the spatial expression pattern of white were scored in the adult eye as nonuniform patterns of pigmentation. Thirty-six independent P[lacW] transposant lines were collected. These represent 12 distinct pigmentation patterns and probably 21 loci. The spatial pigmentation pattern is due to cis-acting suppression of white+ expression, and the suppression probably depends on cell position rather than cell type. The mechanism of suppression differs from inactivation by heterochromatin. In addition, activation of lacZ in P[lacW] occurs also in specific patterns in imaginal discs and embryos in many of the lines. The expression patterns of white+ and lacZ may reflect the activity of regulatory elements belonging to an endogenous gene near each P[lacW] insertion site. We speculate that these putative POSE (position-specific expression) genes may have a role in pattern formation of the eye as well as other imaginal structures. Three of the loci identified are optomotor-blind, engrailed and invected. teashirt is also implicated as a candidate gene. We propose that this "silencer trap"' may be an efficient way of identifying genes involved in imaginal pattern formation.